UPAYA MENGATASI LEARNING LOSS SELAMA PANDEMI COVID-19 DI DAERAH TERTINGGAL - Manganju Manik; Herdina Sinaga (Universitas Islam Sultan Agung, 2022)
This research used a qualitative descriptive approach which aimed to identify the efforts made to solve learning loss in students during the Covid-19 pandemic in remote areas, Junior high school SMP Negeri 2 Siberut Utara and Senior high school SMA Negeri 1 Siberut Utara. Learning loss is a condition where students lose their knowledge, skills, and abilities in the learning process. Data collection techniques used in this research were observation, interviews and documentation. In this case, the researcher saw directly and studied the problems found in the field. The results showed that there were three efforts made to prevent or reduce learning loss conditions for students in remote areas, namely: (1) Efforts through the implementation of online learning using WA groups (WAG), (2) Efforts through the implementation of offline learning by doing home visit, and (3) Efforts through the implementation of offline learning by setting a certain schedule in schools.